Application of Three Bar Truss Problem among Engineering Design Optimization Problems using Artificial Atom Algorithm - Erdogan Yildirim, Ayse; Karci, Ali (Ieee, 2018)
Optimization is all of the transactions made in order to search for the ideal. In the real world, it is needed to optimization in many field. For this reason, optimization algorithms are popular topics that are frequently studied. In this study, it is focused on three bar truss problem which is one of the optimization problem in the engineering field. Artificial Atom Algorithm which is a new chemistry-based meta-heuristic optimization algorithm was used to solve this problem. The obtained results were compared with a Swarm Optimization Approach, Cuckoo Search Algorithm, Bat Algorithm, Mine Blast Algorithm and Cricket Algorithm which were used to solving the same problem.
International Conference on Artificial Intelligence and Data Processing (IDAP) -- SEP 28-30, 2018 -- Inonu Univ, Malatya, TURKEY
Keywords: Artificial intelligence; Computational intelligence; Meta-heuristic algorithms; Artificial atom algorithm; Optimization; Engineering design optimization problem